Reading : - Ladousse, Gillian Porter (Oxford Univ. Press, 1995)
This book helps students to become more aware of the different strategies used in reading. The units are arrangedthematically, with a variety of texts that include excerpts from books, newspaper and magazine articles, afable, a short story and a short play.